1996
DOI: 10.1021/ja9603721
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Aspects of RGD-Containing Cyclic Pentapeptides as Highly Potent and Selective Integrin αVβ3Antagonists

Abstract: The R V β 3 integrin is implicated in human tumor metastasis and in angiogenesis. The design of lowmolecular-mass R V β 3 antagonists by "spatial screening" led to the highly active peptides c(RGDFV) and c(RGDFV).Here the influence of the amino acids in positions 4 and 5 flanking the RGD-sequence on the inhibition of vitronectin and fibrinogen binding to the isolated R V β 3 and R IIb β 3 receptors was investigated. The influence of the side chain and the backbone conformation on activity and selectivity was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
588
1
23

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(630 citation statements)
references
References 61 publications
18
588
1
23
Order By: Relevance
“…As RGD-containing proteins or peptides modeled after the RGD binding sequence on the fibrinogen alpha-chain could block the platelet glycoprotein IIb/llla, a receptor for fibrinogen, and effectively inhibit aggregation, they might be useful for treatment of thrombotic diseases [1][2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As RGD-containing proteins or peptides modeled after the RGD binding sequence on the fibrinogen alpha-chain could block the platelet glycoprotein IIb/llla, a receptor for fibrinogen, and effectively inhibit aggregation, they might be useful for treatment of thrombotic diseases [1][2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…To study the functional conformation of the RGD motif, native RGD-containing proteins, synthetic peptides as well as engineered proteins have been employed [2][3][4][5]. It was proposed that high flexibility of RGD motif region is critical to its function and conformational constraint is also important for the functional roles of RGD motif [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…cRGD peptide selectively recognizes a v b 3 and a v b 5 integrins, 27 and previous studies showed that a v b 3 and a v b 5 are abundantly expressed on endothelial cells and smooth muscle cells in vascular lesions. [28][29][30] PEG-PAsp(DET) micelles installed with cRGD (cRGD-PEG-PAsp (DET) micelles) were applied to endothelial cells and vascular smooth muscle cells in vitro and also to rat carotid artery with neointimal hyperplasia, and the efficacy of gene transfer was evaluated as compared with that of ligand-free PEG-PAsp(DET) micelles.…”
Section: Introductionmentioning
confidence: 86%
“…27 For covalent linking of such cyclopeptides, modified or unmodified -amino lysine side chains were often used. [28][29][30][31][32] Recently Cu-catalyzed click reaction was performed at such a RGD-containing cyclopeptide wherein prior the lysine amino group was transferred into an azido group. 30 In another way the lysine amino group was acylated by propiolic acid and used to introduce an RGD-cyclopeptide into xylose by click chemistry.…”
Section: ____________________________________________________________mentioning
confidence: 99%